Absence of High-mass Prestellar Cores in the Orion Giant Molecular Cloud - Jiao, Wenyu; Ke Wang; Xu, Fengwei (The Astronomical Journal, 2024)
A fundamental difference between “core-fed” and “clump-fed” star-formation theories lies in the existence or absence of high-mass cores at the prestellar stage. However, only a handful of such cores have been observed. Here, different than previous search in distributed star-formation regions in the Galactic plane, we search for high-mass prestellar cores in the Orion GMC, by observing the seven most massive starless cores selected from previous deep continuum surveys. We present ALMA Atacama Compact Array Band 6 and Band 7 continuum and line observations toward the seven cores, in which we identify nine dense cores at both bands. The derived maximum core mass is less than 11 M ⊙, based on different dust temperatures. We find no high-mass prestellar cores in this sample, aligning with the results of previous surveys, thereby challenging the existence of such cores in Orion. Outside Orion, further detailed studies are needed for remaining high-mass prestellar core candidates to confirm their status as massive, starless cores.